Effect of Difference Bulb Size Seedling and Application of Various Doses Nitrogen on the Growth and Yield of Shallot (Allium ascalonicum L.) - Vicky Hardiansyah; Bambang Guritno (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2022)
Shallots are plants that are very responsive to changes in environmental conditions. Onion production data shows that several regions in Indonesia experienced a decline in production. The purpose of this study was to study the effect of differences in the size of the bulbs of shallot seedlings and the application of various doses of nitrogen on the growth and yield of shallots (Allium ascalonicum L.). The research was carried out in Laden Village, Pamekasan District, Pamekasan Regency, Madura on 10 February 2021 - 4 April 2021. The tools used included hoes, water can, nameplates, permanent markers, cutters, rulers, digital scales, writing instruments, and camera. The materials used include shallot seeds of the Blue Lancor variety, urea fertilizer, KCL, SP-36, and fungicides. The study used a factorial randomized block design with 3 replications, the first factor being seed tuber size, consisting of 3 levels and doses of nitrogen fertilizer. S1 = small tubers (< 5 g), S2 = medium tubers (8-10 g), and S3 = large tubers (≥ 13 g). The second factor is the dose of nitrogen fertilizer consisting of 4 levels, namely D1 = 150 kg ha-1, D2 = 200 kg ha-1, D3 = 250 kg ha-1, and D4 = 300 kg ha-1. 5% and further tested with BNJ level 5%. The results showed that increasing the size of the onion seed bulbs could increase growth and yield. the use of nitrogen dose can be increased along with the increase in the size of the tubers used. Based on the yield and quality of tubers, the treatment of medium seed tubers (8-10 g) with a nitrogen dose of 200 kg ha-1 gave good results